To study consumer preference @ different market with the special reference to Pune region. - Ranjan, Dr.Nitin; Dubey, Mr.Amit; Singh, Ms.Nutan (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The retail industry is one of the fastest growing sectors in India, having the world’s second largest place in Consumer market. In market potential India Ranks 5th after United States, China, Brazil and Canada whereas India’s net Retail Sales are quite significant among emerging and developed nations, the country ranks 3rd after China and Brazil. It comprises organized and unorganized sectors which is one of the fastest growing industries in India. Indian Retail Industry is growing fromUS330 billion in 2007 to US640 billion by 2015. New FDI norms had tempted all the major World Retailers towards Indian Market. With the advent of so many indigenous and renowned foreign players, Indian consumers are getting very enriching experiences. Market is flooded with different variety of products as well as customers are enjoying so many discounts at different places at the same time some of them still prefer shopping from unorganized market. This changing scenario of Retail Sector attracts the attention of scholars. From this paper Researchers have found the consumer preferences in different market with special reference to Pune region, Maharashtra. The paper reveals the preference of new era Consumer. The Research Methodology used was simple random sampling method with for the sample size of 126 odd people from. Pune region, Maharashtra.